2020
DOI: 10.3390/cryst10060521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bi Substitution on Structural and AC Magnetic Susceptibility Properties of Nd1−xBixMnO3

Abstract: This study synthesizes the neodymium-based manganites with Bi doping, Nd1−xBixMnO3 (x = 0, 0.25 and 0.50) using the solid-state reaction route. The crystal structural, morphological and magnetic properties were determined using X-ray diffraction (XRD), fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM) and AC magnetic susceptibility. The Rietveld refinement confirmed that the compounds were in the single-phase orthorhombic structure of the NdMnO3 with Pbnm space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…These articles were related to the determination of the effects of the addition of various nanoparticles (GaF 3 , ZnF 2 , Zn(BF 4 ) 2 and Ga 2 O 3 ) on the activity of CsF-RbF-AlF 3 flux and the mechanical behavior of Al/steel brazed joints. Among others, it was shown that the CsF-RbF-AlF 3 flux doped with GaF 3 obtained the maximum spreading area, both on 6061 aluminum alloy and Q235 low-carbon steel, and reached the highest shear strength of 126 MPa.Nur Baizura Mohamed et al [6] have studied the effect of Bi substitution on the structural and magnetic susceptibility properties of Nd 1−x Bi x MnO 3 . The XRD analysis and Rietveld refinement show the pattern corresponding to the perovskite-type NdMnO 3 , which crystallizes in the orthorhombic system with main peak at (121) hkl plane with the Pbnm space group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These articles were related to the determination of the effects of the addition of various nanoparticles (GaF 3 , ZnF 2 , Zn(BF 4 ) 2 and Ga 2 O 3 ) on the activity of CsF-RbF-AlF 3 flux and the mechanical behavior of Al/steel brazed joints. Among others, it was shown that the CsF-RbF-AlF 3 flux doped with GaF 3 obtained the maximum spreading area, both on 6061 aluminum alloy and Q235 low-carbon steel, and reached the highest shear strength of 126 MPa.Nur Baizura Mohamed et al [6] have studied the effect of Bi substitution on the structural and magnetic susceptibility properties of Nd 1−x Bi x MnO 3 . The XRD analysis and Rietveld refinement show the pattern corresponding to the perovskite-type NdMnO 3 , which crystallizes in the orthorhombic system with main peak at (121) hkl plane with the Pbnm space group.…”
mentioning
confidence: 99%
“…Nur Baizura Mohamed et al [6] have studied the effect of Bi substitution on the structural and magnetic susceptibility properties of Nd 1−x Bi x MnO 3 . The XRD analysis and Rietveld refinement show the pattern corresponding to the perovskite-type NdMnO 3 , which crystallizes in the orthorhombic system with main peak at (121) hkl plane with the Pbnm space group.…”
mentioning
confidence: 99%